Peningkatan Pengetahuan Ibu terhadap Gizi dan Keterampilan Olah Daun Beluntas untuk Meningkatkan Produksi ASI Kota Padang - Yussie Ater Merry; Aprizal Ponda; Neni Fitra Hayati; Novelasari; Alsri Windra Doni (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Beluntas leaves (Pluchea Indicha Less) are one of the local medicinal plants that contain galaktogogum, which is believed to increase breast milk production. The method of this community service activity is in the form of counseling, training on processing beluntas leaves which is supported by videos and pocket books and leaflets. This activity aims to provide health education about nutrition and skills in processing beluntas leaves to increase breast milk production for breastfeeding mothers and the use of videos, pocket books and leaflets for breastfeeding mothers in the working area of the Air Winter Health Center. The results of the activity based on interviews with questionnaires showed that the average value was The average knowledge of breastfeeding mothers before (post test) counseling was 52.8% and after counseling the average value was 70.56%. Based on these average results, there was an increase in knowledge of breastfeeding mothers by 17.76%. Conclusion: There was an increase in knowledge of breastfeeding mothers after being given health education about increasing mothers' knowledge of nutrition and skills in processing beluntas leaves to increase breast milk production. It is hoped that the Aia Winter Health Center can provide knowledge to breastfeeding mothers about breastfeeding mothers' nutrition and skills in processing beluntas leaves using video media, leaflets and pocket books.